2019
DOI: 10.1108/gkmc-11-2018-0094
|View full text |Cite
|
Sign up to set email alerts
|

The use and continuance use of social media applications by small and medium enterprises in Kuwait

Abstract: Purpose The purpose of this study is to explore the use and continued intention to use six social media applications (SMAs) (i.e., Facebook, Twitter, YouTube, LinkedIn, Skype and Instagram) by small- and medium-sized enterprises (SMEs) in Kuwait. Design/methodology/approach A survey of 357 SMEs in Kuwait was conducted to achieve the study objectives. Findings The study results showed that SMEs mostly used application was Facebook (by more than three quarters of the SMEs), and the least used one was LinkedI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 28 publications
1
17
0
2
Order By: Relevance
“…Risk (Harris & Rae, 2009;Ahamat et al, 2017;Alzougool, 2019, Ndiege, 2019 and available resources (Grimmer et al, 2017;Grimmer et al, 2018;Olsson & Bernhard, 2020), which included knowledge (Jones et al, 2015;Chatterjee & Kumar Kar, 2020;Kwon et al, 2021;Salam et al, 2021), time (Jones et al, 2015;He et al, 2017;Lepkowska-White et al, 2019), human capacity (Durkin et al, 2013;Jones et al, 2015;Olsson & Bernhard, 2020) and costs (Dlodlo & Dhurup, 2010;Oji et al, 2017;Chatterjee & Kumar Kar, 2020;Kwon et al, 2021) were concluded as barriers to social media in other studies, which mirrored concerns identified in the current study.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Risk (Harris & Rae, 2009;Ahamat et al, 2017;Alzougool, 2019, Ndiege, 2019 and available resources (Grimmer et al, 2017;Grimmer et al, 2018;Olsson & Bernhard, 2020), which included knowledge (Jones et al, 2015;Chatterjee & Kumar Kar, 2020;Kwon et al, 2021;Salam et al, 2021), time (Jones et al, 2015;He et al, 2017;Lepkowska-White et al, 2019), human capacity (Durkin et al, 2013;Jones et al, 2015;Olsson & Bernhard, 2020) and costs (Dlodlo & Dhurup, 2010;Oji et al, 2017;Chatterjee & Kumar Kar, 2020;Kwon et al, 2021) were concluded as barriers to social media in other studies, which mirrored concerns identified in the current study.…”
Section: Discussionsupporting
confidence: 74%
“…This consideration influenced the level of social media activity undertaken by the respondents. The findings suggest that negative feedback is part of social network platform feedback and the result was consequent of the manner in which the customer feedback was handled (Bae & Zamrudi, 2018;Ndiege, 2019;Alzougool, 2019).…”
Section: Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the initial intention to use technology is not enough. It is essential also to explore and understand the continuance intention to use technology; aspects that would encourage users to stay loyal and keep using the technology (C. Kim et al 2010 )(Alzougool 2019 )(Bölen 2020 ). Companies have invested their resources to develop technologies based on users’ needs and requirements.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%